Modelling the supply chain swap problem in the petroleum industry. (13th November 2008) - Al-Husain, Raed; Assavapokee, Tiravat; Khumawala, Basheer
This paper is motivated by the need for developing well-structured methodologies and mechanisms that enable an efficient coordination of swap/exchange transactions among same-level supply chain partners in the petroleum and energy industries. A mathematical model that can capture the complexity in the swap transactions between two companies is presented. The model is then applied to a real case study from the petrochemicals industry, and the solutions of the model are evaluated and their performances are compared to those of current industry practices.